2017
DOI: 10.1101/099853
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ancient antagonism between CELF and RBFOX families tunes mRNA splicing outcomes

Abstract: Over 95% of human multi-exon genes undergo alternative splicing, a process important in normal development and often dysregulated in disease. We sought to analyze the global splicing regulatory network of CELF2 in human T cells, a well-studied splicing regulator critical to T cell development and function. By integrating high-throughput sequencing data for binding and splicing quantification with sequence features and probabilistic splicing code models, we find evidence of splicing antagonism between CELF2 and… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 69 publications
1
7
0
Order By: Relevance
“…Rbfox binding motifs are found to be co-enriched with MBNL and CELF motifs around the same groups of exons in human, mouse and chicken (Bland et al, 2010;Kalsotra et al, 2008;Merkin et al, 2012). Rbfox1 and MBNL co-regulate a significant number of alternative events altered in DM1 skeletal muscle (Klinck et al, 2014), while CELF2 and Rbfox2 co-regulate and co-bind introns flanking exons regulated in cardiac development or with altered expression in hearts of a Type I diabetes mouse model (Gazzara et al, 2017). CELF2 moreover represses Rbfox2 expression in heart, and overexpression of CELF1/2 or depletion of Rbfox2 leads to the same changes in splicing direction and magnitude (Gazzara et al, 2017).…”
Section: Rbfox1-mediated Splicing Is Subject To Cross-regulatory Interaction With Bru1mentioning
confidence: 97%
See 2 more Smart Citations
“…Rbfox binding motifs are found to be co-enriched with MBNL and CELF motifs around the same groups of exons in human, mouse and chicken (Bland et al, 2010;Kalsotra et al, 2008;Merkin et al, 2012). Rbfox1 and MBNL co-regulate a significant number of alternative events altered in DM1 skeletal muscle (Klinck et al, 2014), while CELF2 and Rbfox2 co-regulate and co-bind introns flanking exons regulated in cardiac development or with altered expression in hearts of a Type I diabetes mouse model (Gazzara et al, 2017). CELF2 moreover represses Rbfox2 expression in heart, and overexpression of CELF1/2 or depletion of Rbfox2 leads to the same changes in splicing direction and magnitude (Gazzara et al, 2017).…”
Section: Rbfox1-mediated Splicing Is Subject To Cross-regulatory Interaction With Bru1mentioning
confidence: 97%
“…Many developmentally-regulated, alternatively spliced exons in vertebrate muscle have binding sites for both FOX and CELF family RNA-binding proteins, and in heart notably appear to be antagonistically co-regulated by CELF2 and RBFOX2 (Bland et al, 2010;Gazzara et al, 2017). Thus, we next checked if Rbfox1 and Bru1 co-regulate alternative splicing in Drosophila muscle.…”
Section: Rbfox1 and Bruno1 Co-regulate Alternative Splice Events In Ifmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, a number of Rbfox binding motifs (GCAUG) and CLIP peaks are located just downstream of these exons (Fig 4c, right), where these proteins enhance inclusion [13]. These observations motivated additional study in human T cells where we found Celf2 is a potent repressor of Rbfox2 [6], suggesting that a similar indirect mechanism may be at play in murine muscle and heart where Celf overexpression represses Rbfox proteins to drive splicing changes in these and other targets.…”
Section: Resultsmentioning
confidence: 99%
“…The combinatorial functions of CELF2 and its interactions with other RBPs (e.g. RBFOX) might allow an elaborate regulation of NPC fates through the precise control of mRNAs at different stages of gene expression (Gazzara et al, 2017;Zhang et al, 2016).…”
Section: Discussionmentioning
confidence: 99%